Community Participation in Village Fund Management within Palakka District, Bone Regency of South Sulawesi, Indonesia - Ayub, Zulkifli; Rianti, Marliah; Awaluddin, M.; Triadi, Feby (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
A village as the smallest legal community unit has territorial boundaries that are authorized to regulate and manage the interests of its community based on local origins and customs which are recognized and respected by the state. This study aims to analyze the form and level of community participation in the management of Village Funds in Palakka District, Bone Regency, and to analyze community participation in the management of Village Funds in Palakka District with participatory criteria. This research will use a descriptive method with a qualitative approach. The location of this research will be carried out in Palakka District, Bone Regency. The instruments that will be used in this research are observation, interview, and documentation. Two data collection techniques will be used in this study, namely observation, and interviews. Determination of informants in this study using purposive sampling. The stages of this research consisted of 5 stages, namely the preliminary stage, preparation, implementation, testing, and data analysis stages. Based on the results of the study, it was found that community participation in the process of allocating village funds in Palakka Subdistrict, Bone Regency was high at the stage of assessing the condition of the village at the hamlet level with the participation of attendance, ideas, energy, and funds. However, it is low at the stage of drafting the village plan, village workshops, and the implementation of the village level Musrembang in the form of brainstorming, personnel participation, and social participation.